2008
DOI: 10.1631/jzus.b0720235
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery (VATS) for bilateral primary spontaneous pneumothorax

Abstract: Abstract:Objective: To review our experience of the treatment of bilateral primary spontaneous pneumothorax (PSP) by video-assisted thoracoscopic surgery (VATS). Materials and methods: Retrospective chart review was followed by an on-clinic or telephone interview. Patients were cared for by one thoracic surgeon in four medical centers or community hospitals in Northern and Central Taiwan. Thirteen patients with bilateral PSP underwent bilateral VATS simultaneously or sequentially from July 1994 to December 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Primary spontaneous pneumothorax (PSP), which is defined as a pneumothorax without underlying lung disease, predominantly occurs in young, thin males. It is usually caused by ruptured pleural blebs or bullae (Abdala et al, 2001;Chen Y.J. et al, 2008).…”
Section: Pneumothorax Definition and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary spontaneous pneumothorax (PSP), which is defined as a pneumothorax without underlying lung disease, predominantly occurs in young, thin males. It is usually caused by ruptured pleural blebs or bullae (Abdala et al, 2001;Chen Y.J. et al, 2008).…”
Section: Pneumothorax Definition and Classificationmentioning
confidence: 99%
“…Chemical pleurodesis by minocycline injection, which has been developed in our group (Luh et al, 1996), has been shown to be a safe and convenient procedure that can reduce the rate of recurrence after VATS in a retrospective or prospective randomized trial by colleagues (Chen et al, 2004;2006). However, we do not routinely perform this procedure because it frequently results in intense chest pain and fever, and this additional procedure is only preserved for patients with persistent air-leakage or a higher risk of recurrence, such as multiple or huge bullae (Luh et al, 2004;Luh and Tsao, 2007;Chen Y.J. et al, 2008).…”
Section: Surgical Management Of Pspmentioning
confidence: 99%
“…Because talc is no longer permitted to be used at human body since 2000 in Taiwan, we used pleural electrocauterization for pleurodesis combined with postoperative minocin pleurodesis for some of our patients and can achieve equivalent results (Chen et al, 2008;Hsu et al, 2009). The cauterization was applied most densely on the diaphragmatic surface and lower parietal pleura, and also applied on upper parietal pleura, but with less dense electrocauterization spots.…”
Section: Fig3 Demographic Information and Previous Strategies Of Thementioning
confidence: 99%
“…( 5 , 6 ) According to the literature, most lung bullae are bilateral, resulting in bilateral pneumothorax. ( 8 ) Therefore, it is worth discussing how to perform one-stage bullectomy for the treatment of bilateral SP. One-stage sequential bilateral VATS bullectomy has been considered the best choice.…”
Section: Discussionmentioning
confidence: 99%